Associations between inflammation, coagulation, cardiac strain and injury, and subclinical vascular disease with frailty in older men: a cross-sectional study - Libby Ellins (BMC Geriatrics, 2022)
BackgroundInflammation, coagulation activation, endothelial dysfunction and subclinical vascular disease are cross-sectionally associated with frailty. Cardiac-specific biomarkers are less-well characterised. We assessed associations between these and frailty, in men with, and without, cardiovascular disease (CVD).MethodsCross-sectional analysis of 1096 men without, and 303 with, CVD, aged 71–92, from the British Regional Heart Study. Multinominal logistic regression was performed to examine the associations between frailty status (robust/pre-frail/frail) and, separately, C-reactive protein (CRP), interleukin-6 (IL-6), tissue plasminogen activator (tPA), D-dimer, von Willebrand factor (vWF), high-sensitivity cardiac troponin-T (hs-cTnT), N-terminal pro B-type natriuretic peptide (NT-proBNP) (all natural log-transformed), and, in men without CVD, carotid intima-media thickness (CIMT), carotid-femoral pulse wave velocity (cfPWV), carotid distensibility coefficient (DC), and ankle-brachial pressure index (ABPI), adjusted for age, renal function, BMI, social class, smoking, polypharmacy, cognition, multimorbidity and systolic blood pressure. Explanatory variables with p < 0.05 were carried forward into mutually-adjusted analysis.ResultsIn men without CVD, higher CRP, IL-6, vWF, tPA, hs-cTnT, NT-proBNP, cfPWV, and lower DC were significantly associated with frailty; mutually-adjusted, log IL-6 (OR for frailty = 2.02, 95%CI 1.38–2.95), log hs-cTnT (OR = 1.95, 95%CI 1.24–3.05) and DC (OR = 0.92, 95%CI 0.86–0.99) retained associations. In men with CVD, higher CRP, IL-6, and hs-cTnT, but not vWF, tPA, NT-proBNP or D-dimer, were significantly associated with frailty; mutually-adjusted, log hs-cTnT (OR 3.82, 95%CI 1.84–7.95) retained a significant association.ConclusionsIn older men, biomarkers of myocardial injury are associated with frailty. Inflammation is associated with frailty in men without CVD. Carotid artery stiffness is associated with frailty in men without CVD, independently of these biomarkers.